2008
DOI: 10.1007/s00464-008-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early outcomes for laparoscopic ventral hernia repair between nonobese and morbidly obese patient populations

Abstract: No significant difference in the incidence of perioperative complications or recurrence after LVHR was observed between the morbidly obese patients and the non-morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 20 publications
1
38
0
3
Order By: Relevance
“…La mediana del diámetro mayor de los defectos reparados fue 6 cm (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). 67,7% de los defectos reparados correspondieron a hernias incisionales, un 26% (n = 33) de los casos eran recidivas de reparaciones anteriores, esteroidales y paracetamol por horario.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…La mediana del diámetro mayor de los defectos reparados fue 6 cm (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). 67,7% de los defectos reparados correspondieron a hernias incisionales, un 26% (n = 33) de los casos eran recidivas de reparaciones anteriores, esteroidales y paracetamol por horario.…”
Section: Resultsunclassified
“…Existen controversias respecto a la reparación de hernias ventrales en pacientes sometidos a cirugía bariátrica, debido a que la obesidad es, por si mismo, un factor que determina recidiva herniaria 7 . Se ha descrito en estos pacientes un porcentaje de recidiva que oscila entre un 3 y 8,3% 8,9 , sin embargo, experiencias recientes estiman que la recidiva entre obesos y no obesos sería similar 10 . En nuestra serie, no se registran complicaciones perioperatorias en este subgrupo de pacientes y se observó recidiva en sólo 3 casos cuyos diámetros de defecto superaban los 10 cm.…”
Section: Discussionunclassified
“…The average recurrence rate for LVHR is less of 4% and depends of defect type (primary or incisional) and size, mesh defect overlap and type of mesh fixation (apparently transfascial sutures have an advantage in term of recurrence) [7][8][9][10][11][12]. However a recent meta-analysis about mesh fixation devices failed to demonstrate the advantages of transfascial sutures [14].…”
Section: Discussionmentioning
confidence: 99%
“…The technique is especially preferred for medium size parietal defects (less of 10 cm in diameter) in obese patients because it reduces the wound infection rate as well as overall morbidity [7,10,11]. However there are several relative contraindications as large parietal defects (over 10 cm in diameter) and severe comorbidities (contraindication for laparoscopy and general anesthesia) [7].…”
Section: Patients' Selectionmentioning
confidence: 99%
“…Some studies showed that laparoscopic repair has advantages in length of hospital stay, postoperative pain and social reinsertion, but the costs are higher than in the open surgery [3].…”
Section: Introductionmentioning
confidence: 99%